Zasady ogólne prawa ochrony środowiska na tle konstytucyjnej zasady zrównoważonego rozwoju - Haładyj, Anna (General principles of environmental protection legislature in the light of constitutional principle of sustainable development, 2007)
The main part of the present study focuses on the principle of sustainable development itself and what is meant by this term and what are the legał effects of the recognition of sustainable development principle as an operation guideline, directive and a legał standard binding the public authorities and finally - as a legał principle. The expression “legał principle” denotes the binding legał standard perceived as particularly important for a given legał system or its part (e.g. one or few branches of law). This very character - fundamental, extremely important is typical of the principle of sustainable deyelopment. It is a legał principle of a directive quality, that is, a binding legał principle of fundamental character, because it includes an order (ban) of specific behaviour. The second part of this paper presents the relationship between the principle of sustainable deyelopment and other generał principles of enyironment protection law, regardless of their legał character (principles of law, rules of law, descriptive principles). The following functions of the generał principles of enyironment protection law result from this fact: legislative (determine the legislative direction), interpretational (they are a guideline influencing the interpretation and application of law) and the function of a conflict standard, because they determine the application of certain low-level legał standards in case there is a conflict of standards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 136-145